Cultural intelligence and its relation to the quality of life among fresh students at Prince Sattam bin Abdulaziz University, from the perspectives of faculty members - Al-Rashidi, Anwar Hammad (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the correlation of cultural intelligence with the quality of life in fresh students at Prince Sattam bin Abdulaziz University. The study targeted faculty members working at the university; the sample included 90 individuals. The study adopted a correlational descriptive research design, and research instruments included scales for measuring cultural intelligence and quality of life. The study obtained several findings, most importantly the following: the levels of cultural intelligence among fresh students were rated low; the quality of life among students was rated low; and cultural intelligence was found to be correlated with the levels of cultural intelligence and quality of life among fresh students at Prince Sattam bin Abdulaziz University, from the perspectives of faculty members. Findings of the study indicate that cultural intelligence is an important enabler for improving fresh students’ quality of life. Therefore, promoting cultural intelligence should be taken into careful consideration by university leadership, especially in universities that annually receive large numbers of foreign students. The study presents research suggestions and practical recommendations that include the following: conducting similar studies targeting the contexts of other universities across Saudi Arabia; launching awareness campaigns at Saudi universities that focus on educating students on the value of understanding and respecting diverse cultures from around the world.